2015
DOI: 10.1038/cdd.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic translocation, aggregation, and cleavage of TDP-43 by enteroviral proteases modulate viral pathogenesis

Abstract: We have previously demonstrated that infection by coxsackievirus B3 (CVB3), a positive-stranded RNA enterovirus, results in the accumulation of insoluble ubiquitin-protein aggregates, which resembles the common feature of neurodegenerative diseases. The importance of protein aggregation in viral pathogenesis has been recognized; however, the underlying regulatory mechanisms remain ill-defined. Transactive response DNA-binding protein-43 (TDP-43) is an RNA-binding protein that has an essential role in regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 58 publications
(99 reference statements)
1
55
1
Order By: Relevance
“…Our conclusion is supported by three lines of evidence. First, EV71 and 2A still blocked tSG formation in cells expressing 3C cleavage-resistant G3BP (G3BP Q326E ) ( Fig 3D and 3E , S4D, S4E , S5D and S5E Figs), which contradicts previous findings [ 21 , 38 , 49 ]. We speculate that most of the viruses failed to replicate in cells expressing G3BP Q326E , because G3BP exhibits antiviral activity against several picornaviruses [ 53 ], thus resulting in an eight-fold reduction in viral titer and tSG formation rescue [ 21 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Our conclusion is supported by three lines of evidence. First, EV71 and 2A still blocked tSG formation in cells expressing 3C cleavage-resistant G3BP (G3BP Q326E ) ( Fig 3D and 3E , S4D, S4E , S5D and S5E Figs), which contradicts previous findings [ 21 , 38 , 49 ]. We speculate that most of the viruses failed to replicate in cells expressing G3BP Q326E , because G3BP exhibits antiviral activity against several picornaviruses [ 53 ], thus resulting in an eight-fold reduction in viral titer and tSG formation rescue [ 21 ].…”
Section: Discussioncontrasting
confidence: 77%
“…TDP-43 is then cleaved by 3C pro at Q327, generating two fragments. The C -terminal fragment of TDP-43 is rapidly degraded, whereas the N -terminal product negatively regulates the function of native TDP-43 [ 123 ]. These processes benefit viral replication.…”
Section: The Role Of the Pathogenic Processmentioning
confidence: 99%
“…Thus, TDP-43 is subject to nuclear-cytoplasmic shuttling and mediates RNA-associated functions, mRNA splicing, microRNA processing and mRNA transport to the cytoplasm. It has been shown that not only intact TDP-43 but also several CTFs of TDP-43 are incorporated into cytoplasmic IBs (Neumann et al 2006;Fung et al 2015). The 25-kDa TDP-43 CTF ) is also known as TDP25 (Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 99%